2020
DOI: 10.1038/s41586-020-2800-0
|View full text |Cite|
|
Sign up to set email alerts
|

Stellar clustering shapes the architecture of planetary systems

Abstract: Planet formation is generally described in terms of a system containing the host star and a protoplanetary disk 1 – 3 , of which the internal properties (for example, mass and metallicity) determine the properties of the resulting planetary system 4 . However, (proto)planetary systems are predicted 5 , 6 and observed 7 , 8 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(143 citation statements)
references
References 117 publications
6
135
2
Order By: Relevance
“…Another important implication is that measuring the mass loss rate in different UV environments allows one to explore when external photoevaporation plays a defining role in disk evolution and planet formation. This will provide new insights about how sensitive planet formation is to the surrounding environments, and shed light on the origin of the diversity of observed exoplanetary systems (e.g., Concha-Ramírez et al 2019;Winter et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another important implication is that measuring the mass loss rate in different UV environments allows one to explore when external photoevaporation plays a defining role in disk evolution and planet formation. This will provide new insights about how sensitive planet formation is to the surrounding environments, and shed light on the origin of the diversity of observed exoplanetary systems (e.g., Concha-Ramírez et al 2019;Winter et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Gaia Mission will enable astrometry of hot Jupiters' companions to measure the mutual inclination and further investigations of connections between hot Jupiter occurrence and host star properties. For example, Winter et al (2020) recently found a correlation between hot Jupiters and present-day stellar clustering. If this present-day clustering reflects the early environment, the correlation suggests that dense stellar cluster environments facilitate processes that lead to hot Jupiters.…”
Section: Conclusion and Prospects For Future Characterizationmentioning
confidence: 99%
“…For example, Winter et al. (2020) recently found a correlation between hot Jupiters and present‐day stellar clustering. If this present‐day clustering reflects the early environment, the correlation suggests that dense stellar cluster environments facilitate processes that lead to hot Jupiters.…”
Section: Conclusion and Prospects For Future Characterizationmentioning
confidence: 99%
“…Major efforts are currently being undertaken to link the properties of planetary systems to their large-scale stellar environment, with promising results (e.g. [112][113][114][115]). These studies show that planetary system architectures and planetary properties (e.g.…”
Section: The Influence Of the Stellar And Galactic Environmentsmentioning
confidence: 99%